Legal Protection for Child Victims of Crimes According to The Child Criminal Justice System in Indonesia - RIYADI, Padlah (Indonesia Strategic Sustainability, 2024)
Children are legal subjects and national assets, but every year, juvenile delinquency always increases. One of the efforts to overcome juvenile delinquency is implementing a juvenile criminal justice system. Law Number 3 of 1997 concerning Juvenile Courts specifically regulates the juvenile criminal justice system in Indonesia. The philosophical paradigm of Law Number 3 of 1997 adopts a formal legal approach with an emphasis on punishment. The process of punishment given through formal criminal justice placing children in Correctional Institutions has not succeeded in deterring them. This study uses a normative legal approach method, examining secondary data collected using literature studies using a legislative and conceptual approach. The formulation of policies for handling children must be carried out using a restorative justice approach, a settlement process carried out outside the criminal justice system by involving victims, perpetrators, families of victims and perpetrators, the community and those interested in a crime that occurs to reach an agreement and resolution. This policy is based on the fact that the response or reaction of perpetrators of juvenile delinquency is ineffective without the cooperation and involvement of victims, perpetrators and the community. Restorative justice-based legal protection for children as victims in handling legal cases requires child judges at the District Court to conduct diversion before examining criminal cases of children, as ordered by the SPPA Law. Diversion must be carried out within 7 days, involving related parties, according to the terms and conditions stipulated in the SPPA Law.